Complex dispersions of poloxamers and mesoporous carriers with ibrutinib - Igor A. Dain; Sergey A. Zolotov; Natalia B. Demina; Anna S. Zolotova; Grigorii A. Buzanov; Vasilii M. Retivov; Yevgenii S. Ponomaryov (Elsevier, 2022)
Ibrutinib is an anticancer drug, a Bruton's tyrosine kinase inhibitor with poor solubility in aqueous media. This study reports on the study of the effectiveness of mesoporous carriers based on magnesium aluminometasilicate and poloxamers to improve the solubility and bioavailability of ibrutinib in the form of amorphous solid dispersions. The choice of the most effective composition was made on a parallel study of (a) a physical mixture of ibrutinib with a mesoporous carrier, (b) a solid dispersion with a poloxamer on a non-porous carrier, (c) a dispersion with a poloxamer deposited on a mesoporous carrier. Sample mixtures and dispersions with ibrutinib were tested to establish amorphism by various methods and to determine the solubility in aqueous media. The composition of ibrutinib-poloxamer P407-mesoporous carrier showed the best results in three standard media regarding the solubility of ibrutinib (increase in solubility at pH 1.2 - 129.6%, pH 4.5 - 300.2%, pH 6.8 - 363.3%). This composition became the basis for the tablet formulation and showed the best results in the Dissolution test (the dosage was dissolved in only 10 min of the test in pH 1.2 medium by 98.3%, pH 4.5 - 95.4%, pH 6.8 - 57.3%). These results were superior to those of the original Imbruvica capsules at all points in the study. In conclusion, the resulting formulation was stable under accelerated conditions according to the ICH Q1 Quality Guideline (40 °C, 75% relative humidity, 6 months).